An elevated C-reactive protein level in an inpatient rehabilitation setting after joint replacement: To act or not to act? – that is the question. Issue 8 (26th February 2021) - Aggarwal, Arun; Sinha, Vikram; Chan, Eric; Parapuram, Anuka
Abstract : Abstract: C-reactive protein (CRP) is part of a battery of "routine bloods" performed by residents on patients when they are admitted into a rehabilitation unit. Generally, an elevated CRP is considered to be an indicator of an acute infective process. Numerous studies have indicated that the CRP peaks on the 2nd or 3rd day post total hip arthroplasty (THR) and total knee arthroplasty (TKR) and returns to normal by day 7. When the CRP level remains elevated, it is generally felt that infection should be excluded. We performed a prospective study on 45 consecutive patients admitted into a rehabilitation unit post hip and knee arthroplasty over a 6 months period, to evaluate the incidence of an elevated CRP on admission, to determine whether an isolated elevated CRP on admission to a rehabilitation setting should not be considered as an indicator of an infective process. We found all patients (100%) had elevated CRP's on admission, ranging from 8.6 mg/L to 139.2 mg/L, between days 5–7 post-operatively. By day 14, CRP's reduced, but 91% of patients still had elevated CRP's, ranging from 2.1 mg/L to 47.3 mg/L after THR and 4.8 mg/L to 40 mg/L after TKR at day 14. These results suggest that even in uncomplicated elective joint arthroplasty, CRP's can remain elevated up to 14 days post-procedure, in the absence of an infective process. An isolated elevated CRP on admission to a rehabilitation setting should not be considered as an indicator of an infective process, but rather part of the normal post-operative inflammatory response. The elevated CRP should be monitored and only an upward trend requires further investigation and management.